Diverse use of iron oxide nanoparticles for anticancer therapy - Abayaweera, Gayani Sandeepa (Kansas State University, 2014)
Recent development of a variety of superparamagnetic and ferromagnetic iron/iron oxide (Fe/Fe₃O₄) nanoparticles with different surface chemistry have been widely studied for numerous biological applications such as drug delivery, as diagnostics, hyperthermia and magnetic resonance imaging. The wide applications of Fe/Fe₃O₄ nanoparticles are possible since they exhibit favorable properties as high magnetization ability, are smaller than 100 nm in size, they can be coated with several ligands which allow drug delivery at a specific site and are biocompatible. By using Fe/Fe₃O₄ nanoparticles as drug delivery agents treatment costs and side effects can be reduced, however treatment efficacy can be increased. We have demonstrated that Fe/Fe₃O₄ nanoparticles can be utilized in different methods depending on their properties, to be used as therapeutic agents for cancer treatment. In one method we have taken advantage of the Fe/Fe₃O₄ nanoparticles magnetic ability to produce hyperthermia (heat) in cancer cells when subjected to an alternative magnetic field. Here we use the cell based delivery system since the size of the nanoparticles are small they can be taken up by monocyte/ macrophage like cells for systemic transportation to the inflamed cancer cite. The hyperthermia study was conducted in mice with pancreatic cancer. This study demonstrated that the life expectancy of the mice increased by 31%. In the next method we took the advantage of the surface chemistry of the Fe/Fe₃O₄ nanoparticles and changed it with dopamine-peptide and dopamine-thiosemicarbazone ligands. The advantage of the peptide is to deliver the nanoparticle to its target site and the thiosemicarbazone analogue is used as an iron chelator that would initiate apoptosis in cancer cells. This nanoplatform was tested in 4T1 breast cancer cell line and normal fibroblast cell line and demonstrated that it was effective towards the cancer cell line than the normal cell line at a ratio of 5:1 of thiosemicarbazone analogue : dopamine on the nanoparticle. However further studies are needed to be done to clarify the effectiveness of this nanosystem.
Keywords: Cancer; Peptide; Iron chelator; Nanoparticles; Hyperthermia; Antitumor activity; Chemistry (0485); Nanotechnology (0652)